Deception detection and emotion recognition: Investigating F.A.C.E. software. (18th August 2021) - Curtis, Drew A.
Abstract: Objective: Investigation of deception within psychotherapy has recently gained attention. Micro expression training software has been suggested to improve deception detection and enhance emotion recognition. The current study examined the effects of micro expression training software on deception detection and emotion recognition. Method: The current study recruited 23 counseling psychology graduate students and 32 undergraduate students and randomly assigned them to either a training group or a control group. The training and control group received all the same materials and measures pre- and post-test, with the training group differing by receiving the micro expression training. Results: Findings revealed no significant difference in deception detection between the control group and training group. The training did reveal significant improvement for emotion recognition, specifically in contempt, anger, and fear. State and trait anxiety did not predict deception detection nor did it mediate emotion recognition. No significant difference was found between graduate trainees and undergraduate students. Conclusion: The use of the F.A.C.E. software was not effective for increasing deception detection but did serve to increase emotion recognition. Implications for training, practice, and research are discussed.